A machine learning approach to classification for traders in financial markets. Issue 1 (28th June 2022) - Wright, Isaac D.; Reimherr, Matthew; Liechty, John
Abstract : We introduce new machine learning methods for clustering traders who are actively trading in a modern electronic exchange which uses a matching engine to track aggregate and individual‐level limit order books. Each trader's individual limit order book is centered (with the current best bid and ask prices acting as a central reference), and the patterns in the individual limit order books are identified using a Wasserstein distance. The method is illustrated using simulated limit order book data and limit order book data from a stock exchange in Canada.